The natural radioactivity in water by gross alpha and beta measurements - Bonotto, Daniel Marcos [UNESP]; Bueno, T. O. [UNESP]; Tessari, B. W. [UNESP]; Silva, A. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2009)
An alternative method for evaluating gross alpha and beta radioactivity in water was developed by performing alpha counting using a surface barrier detector and gamma-ray spectrometry using a Nal(Tl) scintillation detector. Several experiments were realized under controlled conditions in the laboratory with the aim of establishing adequate calibration of the systems utilized for performing activity concentration measurements in water samples of variable salinity. Groundwater samples collected at several spas in São Paulo and Minas Gerais States in Brazil were submitted to the developed technique in order to assure its applicability in waters characterized by different Total Dissolved Solids content. The values obtained were compatible with the previous knowledge of the radioactivity of the studied water sources, thus indicating the reliability and usefulness of the method for generating information on investigations focusing environmental aspects and/or the evaluation of the drinking water quality in terms of radiological aspects. (C) 2008 Elsevier Ltd. All rights reserved
Keywords: Gross alpha; Gross beta; Gamma-ray spectrometry; Drinking water quality; Groundwater radioactivity